2013
DOI: 10.1177/1359105313506761
|View full text |Cite
|
Sign up to set email alerts
|

Unreliable item or inconsistent person? A study of variation in health beliefs and belief-anchors to biomedical models

Abstract: Several models for health beliefs grounded in social theories have been extensively used in health-related research. However, the measurement of beliefs, especially the stability of beliefs, is still an understudied area. For example, reliability of an item designed to measure health belief is often confounded with response consistency at the person level, and the problem is often ignored in social research in medicine. To delineate discordant responses to the same item of belief in diabetes, which could be du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…As part of a study of health beliefs and behavior on adults with diabetes who live in rural areas in the U.S. (Arcury et al, 2012; Quandt et al, 2012), the data used in this analysis were collected from the instrument CSMDI, which measures common-sense beliefs about their disease held by individuals with diabetes (Ip et al, 2013c). The CSMDI is composed of a battery of 31 items, which cover beliefs in six different domains—symptoms, causes, consequences, information, behavioral management of diabetes, and medical management of diabetes.…”
Section: Application To Common-sense Beliefmentioning
confidence: 99%
See 2 more Smart Citations
“…As part of a study of health beliefs and behavior on adults with diabetes who live in rural areas in the U.S. (Arcury et al, 2012; Quandt et al, 2012), the data used in this analysis were collected from the instrument CSMDI, which measures common-sense beliefs about their disease held by individuals with diabetes (Ip et al, 2013c). The CSMDI is composed of a battery of 31 items, which cover beliefs in six different domains—symptoms, causes, consequences, information, behavioral management of diabetes, and medical management of diabetes.…”
Section: Application To Common-sense Beliefmentioning
confidence: 99%
“…The reason we used information from both study visits is that the common sense beliefs expressed by the participants could vary substantially across different measuring occasions. The response inconsistency observed in this kind of data is sometimes above and beyond measurement error and reflects a person’s level of ambivalence about a specific belief (Ip et al, 2013c). The poset in Fig.…”
Section: Application To Common-sense Beliefmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue may be compounded by inconsistent interpretation of the behavioural items. Ip et al [44] indicated that such problems could relate to differences in the belief anchors that link a belief to either the biomedical or biopsychosocial belief systems. Those authors explored health and illness beliefs among people with diabetes and found that biomedically-located anchors were reported more consistently than other anchors [44].…”
Section: Discussionmentioning
confidence: 99%
“…This issue may be compounded by inconsistent interpretation of the behavioural items. Ip et al (52) indicated that such problems could relate to differences in the belief anchors that link a belief to either the biomedical or biopsychosocial belief systems. Those authors explored health and illness beliefs among people with diabetes and found that biomedically-located anchors were reported more consistently than other anchors (52).…”
Section: Discussionmentioning
confidence: 99%